Development and Validation of a Tool to Improve Community Pharmacists’ Surveillance Role in the Safe Dispensing of Herbal Supplements - Jairoun, Ammar Abdulrahman; Al Hemyari, Sabaa Saleh; Abdulla, Naseem Mohammed; Shahwan, Moyad; Jairoun, Maimona; Godman, Brian; El-Dahiyat, Faris; Kurdi, Amanj (Frontiers in Pharmacology, 2022)
Background: There has been an appreciable increase in the use of herbal supplements, including immune boosters, during the current COVID-19 pandemic. However, there are concerns with falsified herbal supplements Objectives Developed a new questionnaire that can potentially help community pharmacists with identifying the extent of falsified herbal supplements. Methods: A cross sectional study conducted over nine months among 500 community pharmacies in the UAE. Face-to-face interviews were undertaken using a structured questionnaire, which was subjected to face and content validity, with the content validity index (CVI) computed. Construct validity was tested using an exploratory factor analysis (EFA) via principally component analysis (PCA). The model was then confirmed through Partial confirmatory factor analysis (PCFA). Reliability was assessed via test-retest reliability, internal consistency, item internal consistency (IIC), and intraclass correlation coefficients (ICCs). Results: An instrument compromised of five domains with a 24-item scale was developed with CVI of 0.843. The KMO measure of sampling adequacy was 0.891, and Bartlett’s test of sphericity indicated significance (p-value < 0.001). Confirmation of the subsequent 5-domains was achieved through PCFA using MLA with oblimin rotation. The PCFA obtained values of 0.962 for NFI, 0.977 for CFI, and 0.987 for TLI; all values were greater than 0.95, and the RMSEA value was 0.03 (i.e., less than 0.06). Consequently, the model had a good fit. All domains demonstrated Cronbach’s alpha coefficients above 0.70, with 0.940 for the full instrument. Meanwhile, all items met the IIC correlation standard of ≥ 0.40. The instrument presented good ICC statistics of 0.940 (0.928 – 0.950) as well as statistical significance (p < 0.001). Those participants who had more than 10 experience years more likely to identify falsified herbal supplements compared to those who have 1 to 10 experience years (p < 0.001). Conclusions: This study developed and validated a new instrument to identify safe herbal supplements products, which will help enhance the role of the community pharmacists in safe and effective treatment of suitable patients with herbal supplements.